A changing fishery system: perspectives from crew in the Southern Cape's handline fishery. Issue 2 (4th May 2019) - Gammage, Louise C.; Jarre, Astrid; Mather, Charles
ABSTRACT: Fishers operating on smaller scales are vulnerable to stressors at multiple temporal and spatial scales that drive change in marine social-ecological systems (SES). Apart from natural variability, the effects of anthropogenic change and developmental challenges add to complexity and uncertainty. Fishers need to proactively implement response strategies to achieve sustainable livelihoods and well-being. To do so, the impact and interplay of drivers of change within SES need to be better understood. Participant-led research was conducted with the crew who operate in the small-scale linefishery of the Southern Cape (South Africa) between 2014 and 2015. Fishers' perspectives were recorded using asurvey with 59 households. Specifically, the research seeks to establish what knowledge the crew of the linefishery hold of the drivers of change in their area of operation. The results offer an analysis focusing on the stressors in the natural system, social and economic (sub-)systems, policy and regulatory issues and insights into the fishers' attitude towards change and adaptation options. The research, complimenting previous research, contributes to the understanding of this SES by providing insights into this linefishery which needs to be accounted for when considering future responses to change.